DETERMINANTS OF STUDENT INTEREST IN CHOOSING A STUDY PROGRAM - Singgih Purnomo; Rayhan Gunaningrat (Bajang Institute, 2022)
The Indonesia Career Center Network (ICCN) survey in 2017 showed that 87 percent of Indonesian students chose study programs at universities that did not match their interests. One of the impacts of choosing a study program that is not in my interest is the possibility of delays in completing the education period on time and not maximizing the pursuit of the best results. Seeing these empirical conditions, this study aims to explain whether internal factors or external factors more significantly influence student interest when choosing a study program in higher education. Internal factors are represented by self-motivation, ideals, and desires. Meanwhile, external factors are represented by the image of the university, family support, and previous school support. This research was conducted at Universitas Duta Bangsa Surakarta with a sample of 339 students from various study programs selected at random. Data were collected using a digital questionnaire. The Likert scale became a data measuring tool and was analyzed using the Structural Equation Model (SEM). The results of the analysis show that internal factors have more influence on student interest when choosing a study program at the university level.